Physiological and performance changes in national and international judo athletes during block periodization training - Marques, L.; Franchini, E.; Drago, D.; Aoki, M. S.; Moreira, A. (Biology of Sport, 2017)
Block periodization (BP) has been proposed as an alternative approach for application in the context of high-level sports. Despite its growing acceptance, there is no empirical evidence of BP adoption in high-level judo athletes. Therefore, this study aimed to compare the maximal strength, muscle power, judospecific performances, and hormonal concentration changes of state/national level (NG) and international level (IG) judo athletes subjected to BP. Twenty-one elite judo athletes (international level = 10; 21.7±1.9 years, 167.2±7.6 cm, 67.6±9.4 kg, 15.7±1.9 years of practice; national level = 11; 21.9±3.0 years, 167.5±9.1 cm, 71.8±16.5, 15.9±3.0 years of practice) were subjected to 13-week BP training (5-week accumulation phase [ACP], 5-week transmutation phase [TP], and 3-week realization phase [RP]). The judo-specific performance (SJFT) increased as there was observed a decrease in the SJFT index (final heart rate [HR] (bpm) + HR1 min after the test divided by the number of throws) for both NG (effect size [ES] = 0.83) and IG (ES = 0.53) from ACP to TP (p < 0.05). The row exercise maximal strength decreased (p < 0.05; ES = 1.35) after the ACP but returned to the baseline level after the TP, for the whole group (ES = 1.39). The athletes did seem to cope appropriately with the demands of BP, as besides increases in SJFT performance no significant changes were observed for cortisol and testosterone concentrations. This is the first study to demonstrate that judo athletes from different competitive levels subjected to BP improved SJFT, likely due to an appropriate balance between training loads and recovery. Thus, the BP approach may be a useful alternative periodization strategy for highlevel judo athletes.